KECERDASAN BUATAN: PLAGIARISME DAN PERILAKU MANDIRI SISWA SEKOLAH MENENGAH ATAS DALAM PENGGUNAAN CHATGPT - Adriansyah, Fajar; Aditya, Mochamad; Supriady, Mochammad Aldy; Ramadhan, Wildan (Jurnal Teknologi Komputer dan Informatika, 2024)
Advances in artificial intelligence (AI) through platforms such as ChatGPT offer great potential in supporting high school students' learning, but also pose challenges such as plagiarism and decreased learning independence. This article explores the influence of ChatGPT on student behavior, analyzes the risks and benefits, and proposes strategies for ethical and effective use of AI. This study provides insights for educators and policymakers to maximize the positive impact of AI in education.